Novel psychoactive substances of interest for psychiatry. Issue 1 (February 2015) - Schifano, Fabrizio; Orsolini, Laura; Duccio Papanti, G.; Corkery, John M.
<x xml:space="preserve">Abstract</x> Novel psychoactive substances include synthetic cannabinoids, cathinone derivatives, psychedelic phenethylamines, novel stimulants, synthetic opioids, tryptamine derivatives, phencyclidine‐like dissociatives, piperazines, GABA‐A/B receptor agonists, a range of prescribed medications, psychoactive plants/herbs, and a large series of performance and image enhancing drugs. Users are typically attracted by these substances due to their intense psychoactive effects and likely lack of detection in routine drug screenings. This paper aims at providing psychiatrists with updated knowledge of the clinical pharmacology and psychopathological consequences of the use of these substances. Indeed, these drugs act on a range of neurotransmitter pathways/receptors whose imbalance has been associated with psychopathological conditions, including dopamine, cannabinoid CB1, GABA‐A/B, 5‐HT2A, glutamate, and k opioid receptors. An overall approach in terms of clinical management is briefly discussed.